Current status of fertility and family formation in men with cystic fibrosis. (8th August 2021) - Bourke, Stephen J.; Anderson, Alan; Briggs, Jonathan; Doe, Simon; Echevarria, Carlos; Choudhary, Meenakshi; McEleny, Kevin; Stewart, Jane
Abstract: Men with cystic fibrosis are nearly always infertile due to congenital bilateral absence of the vas deferens, but can undergo assisted reproduction. Ill health may influence reproductive choices. This paper reports data on fertility and family formation in CF including the use of assisted reproduction in a total cohort of 205 men (mean age 30.9, range 16.6–64.3 years) studied over a 10-year period. Overall 102 (49.5%) were single, 52 (25.7%) were married, 48 (23.3%) were in long-term heterosexual relationships, and 3 (1.5%) were in same-sex relationships. One (0.5%) was fertile naturally. In total, 30 children were born to 23 (11%) men by assisted reproduction: 4 used donor sperm and 19 had sperm retrieval and intracytoplasmic sperm injection (ICSI). Two men each adopted two children; 15 (7.3%) men were acting as step-fathers to 20 children from their partners' previous relationships. Overall 41 (20%) men had fatherhood roles. ICSI was unsuccessful in 4 men. A further 16 men were referred for fertility treatment but did not proceed. Of the 19 men having children by ICSI, 3 died leaving 4 children. Men with CF face complex decisions when considering their relationships, fertility and fatherhood.